Top-Down Stereolithography-Based System for Additive Manufacturing of Zirconia for Dental Applications - Kumiko Yoshihara; Noriyuki Nagaoka; Fiona Spirrett; Yukinori Maruo; Yasuhiro Yoshida; Bart Van Meerbeek; Soshu Kirihara (Applied Sciences)
This study investigated the feasibility and effectiveness of a commercial top-down stereolithography (SLA)-based system for the additive manufacturing of zirconia dental prostheses. Yttria-stabilized zirconia–resin slurries were prepared, and zirconia objects were fabricated using a top-down SLA system. Thermogravimetric–differential thermal analysis was used to examine the resin, while X-ray fluorescence spectroscopy and X-ray diffraction were used to analyze the printed samples. The microstructures of additively manufactured and subtractively manufactured zirconia were compared using field emission scanning electron microscopy (FE-SEM) before and after sintering. Biaxial flexural strength tests were also conducted to evaluate mechanical properties. The green bodies obtained via additive manufacturing exhibited uniform layering with strong interlayer adhesion. After sintering, the structures were dense with minimal porosity. However, compared to subtractively manufactured zirconia, the additively manufactured specimens showed slightly higher porosity and lower biaxial flexural strength. The results demonstrate the potential of SLA-based additive manufacturing for dental zirconia applications while also highlighting its current mechanical limitations. The study also showed that using a blade to evenly spread viscous slurry layers in a top-down SLA system can effectively reduce oxygen inhibition at the surface and relieve internal stresses during the layer-by-layer printing process, offering a promising direction for clinical adaptation.